2013
DOI: 10.1371/journal.pone.0082577
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Heat Shock Proteins 27 and 70, p-Akt/p-eNOS and MAPKs by Naringin Dampens Myocardial Injury and Dysfunction In Vivo after Ischemia/Reperfusion

Abstract: Naringin has antioxidant properties that could improve redox-sensitive myocardial ischemia reperfusion (IR) injury. This study was designed to investigate whether naringin restores the myocardial damage and dysfunction in vivo after IR and the mechanisms underlying its cardioprotective effects. Naringin (20–80 mg/kg/day, p.o.) or saline were administered to rats for 14 days and the myocardial IR injury was induced on 15th day by occluding the left anterior descending coronary artery for 45 min and subsequent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Previous studies demonstrated that naringin elevated expression of p-eNOS (Ser1177) and reduced expression of nitrotyrosine in myocardial ischemia reperfusion injury (44). In this study, it was found that oral administration of naringin to fructose fed rats for 4 weeks increased the expression of eNOS and p-eNOS (Ser1177), and decreased the expression of nitrotyrosine in aortic tissues (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies demonstrated that naringin elevated expression of p-eNOS (Ser1177) and reduced expression of nitrotyrosine in myocardial ischemia reperfusion injury (44). In this study, it was found that oral administration of naringin to fructose fed rats for 4 weeks increased the expression of eNOS and p-eNOS (Ser1177), and decreased the expression of nitrotyrosine in aortic tissues (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…The primary antibodies used were against b-actin, caspase-3, IKK-b, NF-jBp65, TNF-a, Bax and Bcl-2 and were detected with HRP-conjugated anti-rabbit/anti-goat secondary antibody. The antibody-antigen complexes were visualized using enhanced chemiluminescence kit (Thermo Scientific) under FluorChem M Protein imaging System (Bucher Biotec AG, Basel Switzerland) and were quantified by Bio-Rad Quantity One 4.4.0 software (BIO-RAD, Hercules, CA, USA) [22].…”
Section: Protein Expression Changesmentioning
confidence: 99%
“…17 Moreover, several studies have suggested that extracellular signalregulated kinase (ERK1/2), 18 5′ AMP-activated protein kinase (AMPK), 19 phosphatidylinositol-3-kinase (PI3 K/AKT), and protein kinase C (PKC) 20 may have a central function in the activation of Nrf2. 26,29,30 However, the molecular mechanisms underlying the protective effects of Nar against anoxia/reoxygenation (A/R)-induced cardiac insult remain poorly defined. 21 Flavonoids are a group of polyphenolic compounds that are common components of the human diet.…”
Section: Introductionmentioning
confidence: 99%